'Hybrid Transitions: Combining Biomass and Solar Energy for Water Heating in Public Bathhouses'. (December 2015) - Sibley, Magda; Sibley, Martin
Abstract: This paper presents and evaluates initiatives taken in Morocco to reduce wood consumption, improve energy efficiency and reduce deforestation due to the operation of hammams (Turkish baths). First, the paper examines the vernacular energy systems used in heritage hammams and their lessons of sustainability. Second, it presents the problems associated with the new hammam furnaces and how they replicate vernacular systems. Third, the various initiatives for more energy efficient systems are presented. These include hybrid solar/biomass hammam systems. The paper evaluates the opportunities for addressing local and global concerns over deforestation and CO2 emissions and discusses various difficulties and challenges.